2016
DOI: 10.1111/modl.12343
|View full text |Cite
|
Sign up to set email alerts
|

The Development of L2 Fluency During Study Abroad: A Cross‐Language Study

Abstract: Examining speech samples from 75 American university students learning 1 of 3 languages (Mandarin, Russian, and Spanish), this article reports on a study of second language (L2) learners’ oral fluency development and its relationship with their gains in holistic proficiency ratings during a semester abroad. In study abroad research, there is a need for large‐scale studies that systematically investigate learners’ L2 development (Kinginger, ; Rees & Klapper, ). To address this need, the project used a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Results focusing on repair fluency demonstrated no change over time for either measure (number of repetitions and corrections per second) a finding similar to Di Silvio et al. () for their L2 Spanish group. A possible explanation for this finding is that increases in learners’ proficiencies (see Huensch & Tracy–Ventura, ; Mitchell et al., ) allowed for an increased ability to monitor and/or repair their speech.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Results focusing on repair fluency demonstrated no change over time for either measure (number of repetitions and corrections per second) a finding similar to Di Silvio et al. () for their L2 Spanish group. A possible explanation for this finding is that increases in learners’ proficiencies (see Huensch & Tracy–Ventura, ; Mitchell et al., ) allowed for an increased ability to monitor and/or repair their speech.…”
Section: Discussionsupporting
confidence: 84%
“…It is a rather robust finding now that participation in study abroad leads to significant gains in oral fluency, particularly for measures such as speech rate, when measured at the end of a stay abroad (Di Silvio et al, 2016;Du, 2013;Mora & Valls-Ferrer, 2012;Towell et al, 1996). However, less is known about the development of oral fluency for stays longer than the typical academic semester or after participants return to their home universities.…”
Section: Fluency and Study Abroadmentioning
confidence: 99%
“…With a larger percentage of students going abroad for shorter periods of time, language educators must carefully consider programmatic designs, set reasonable outcomes for brief sojourns, evaluate the potential for language development, and foster the skills that are described in the World‐Readiness Standards for Language Learners (WRS) (National Standards Collaborative Board, ). It has generally been accepted that immersive experiences abroad provide a valuable learning context for acquiring L2 communication skills (Di Silvio, Diao, & Donovan, ; Kennedy Terry, ; Lafford & Collentine, ; Shiri, ). However, research has shown that language development abroad depends greatly on a range of program and learner factors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While it is widely accepted that frequent and sustained interaction with native speakers facilitates language gain (Allen & Herron, ; Cadd, ; Di Silvio et al, , Pinar, ; Wang, ), proficiency gains have not always been linked to the amount of time students spend with native speakers. For example, Martinsen () investigated a 6‐week program in Argentina and reported no direct correlation between the amount of time participants spent with native speakers and improved oral skills, attributing the results to the repetitive nature of the interactions in which many L2 learners engaged.…”
Section: Program Factorsmentioning
confidence: 99%
See 1 more Smart Citation